Analysis of Natural Convection and Melting in a Separated Cavity with Nano-enhanced Phase Change Material filled wall - Öztop, Hakan Fehmi; Cosanay, Hakan; Biswas, Nirmalendu; Selimefendigil, Fatih (Springer Heidelberg, 2024)
In this study, a new control of the heat transport process utilizing phase-change materials (PCMs), as latent thermal energy storage, and nanofluid flow in a thermal system is explored numerically. The proposed model comprises PCM domain divided square enclosure, filled with two different nanofluids (TiO2 and CuO) heated and cooled, respectively, at the left and right sides of the enclosure. Horizontal walls are adiabatic. The coupled mathematical model comprises phase-change materials, nanofluids, and thermal gradients, which are solved numerically following the finite volume-based approach. The enthalpy-porosity technique is adopted to assess the melting behavior of the PCM domain. The thermo-hydraulic performance of the complex system of nanofluids and the melting process of PCM is assessed for the set of control variables such as Grashof numbers (Gr) and nanoparticle concentration (phi). Analysis revealed that the melting performance of the PCM domain is significantly influenced by the concentration of the nanoparticles on both sides. The results revealed that, for the early stage of the melting process, the thickness of the melted layer strongly depends on the interaction of the thermal gradient inside the cavity. Higher Gr value and phi lead to higher thermal convection in the heated section, which allows the faster melting process of the PCM domain and more amount of thermal energy storage inside the PCM. This transport process further enhances with the increase in the nanoparticles concentrations. A higher Gr value with higher nanoparticle concentrations is always beneficial for the higher amount of thermal energy storage and storage goes up to 35.80%.
Keywords: Phase-change material (PCM); Melting performance; Nanofluids; Heat transfer